EFEKTIFITAS PEMANFAATAN JALAN INSPEKSI SUNGAI KLAMPOK BAGI PENGAWASAN LIMBAH INDUSTRI DI KELURAHAN NGEMPON KECAMATAN BERGAS KABUPATEN SEMARANG - Muh Amin (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The existence of industries in Ngempon Village, Bergas District, Semarang Regency has a high level of activity and is mostly located around the Klampok River, which is part of the Jragung River Basin (DAS). This condition increases the need for an effective industrial waste monitoring system to prevent river pollution. One of the crucial infrastructures that supports such monitoring is the inspection road located along the riverbank. This study aims to analyze the existing condition of the inspection road, assess the level of its utilization effectiveness in industrial waste monitoring, and identify the supporting and inhibiting factors affecting its effectiveness. The research method used is quantitative with a descriptive approach. Data collection was carried out through field observations, interviews, and questionnaires distributed to 44 respondents, consisting of officers from the Environmental Agency, company representatives, and river conservation organizations. Data analysis used a Likert scale based on the dimensions of physical condition, accessibility, monitoring function, and monitoring outcomes. The results show that the condition of the inspection road still has various limitations, including 90% of the road width being less than 2 meters, 30% of the road surface still being dirt, the presence of wild vegetation obstructing access, minimal lighting, and the unavailability of signage and supporting monitoring facilities. Nevertheless, the inspection road has advantages such as close access to waste outlets, fast travel time, and ease of sampling and documentation. The total effectiveness index value of 56.62 indicates that the utilization of the inspection road falls into the moderately effective category, meaning it can support industrial waste monitoring but still faces various obstacles. Therefore, improving the quality of inspection road infrastructure through pavement, vegetation management, provision of lighting, information signs, and other supporting facilities is necessary to enhance the effectiveness of sustainable industrial waste monitoring.